Law and religion in the Roman republic - Tellegen-Couperus, O. E. (Mnemosyne, Supplements, 2012)
Over the past two hundred plus years, scholarship has admired Roman law for being the first autonomous legal science in history. This biased view has obscured the fact that, traditionally, law was closely connected to religion and remained so well into the Empire. Building on a variety of sources - epigraphic, legal, literary, and numismatic - this book discloses how law and religion shared the same patrons (magistrates and priests) and a common goal (to deal with life's uncertainties), and how, from the third century B.C., they underwent a process of rationalization. Today, Roman law and religion deserve our admiration because together they supported and consolidated the growing power of Rome.